The role of sphingosine-1-phosphate in the development and progression of Parkinson’s disease - Wang, Wang; Zhao, Yang; Zhu, Guoxue (Frontiers in Cellular Neuroscience, 2023)
Parkinson's disease (PD) could be viewed as a proteinopathy caused by changes in lipids, whereby modifications in lipid metabolism may lead to protein alterations, such as the accumulation of alphasynuclein (α-syn), ultimately resulting in neurodegeneration. Although the loss of dopaminergic neurons in the substantia nigra is the major clinical manifestation of PD, the etiology of it is largely unknown. Increasing evidence has highlighted the important role of lipids in the pathophysiology of PD. Sphingosine-1-phosphate (S1P), a signaling lipid, has been suggested to have a potential association with the advancement and worsening of PD. Therefore, better understanding the mechanisms and regulatory proteins is of high interest. Most interestingly, S1P appears to be an important target to offers a new strategy for the diagnosis and treatment of PD. In this review, we first introduce the basic situation of S1P structure, function and regulation, with a special focus on the several pathways. We then briefly describe the regulation of S1P signaling pathway on cells and make a special focused on the cell growth, proliferation and apoptosis, etc. Finally, we discuss the function of S1P as potential therapeutic target to improve the clinical symptoms of PD, and even prevent the progression of the PD. In the context of PD, the functions of S1P modulators have been extensively elucidated. In conclusion, S1P modulators represent a novel and promising therapeutic principle and therapeutic method for PD. However, more research is required before these drugs can be considered as a standard treatment option for PD.